Shear Wave Velocity of the Antarctic Upper Mantle from Full Waveform Inversion and Long Period Ambient Seismic Noise ... - Emry, Erica; Hansen, Samantha (U.S. Antarctic Program (USAP) Data Center, 2025)
This dataset provides the shear-wave velocity model resulting from a full-waveform inversion that was constrained using long-period empirical Green's functions extracted from ambient seismic noise. The results are highlighted in Hansen and Emry (2025). ...